Alcohol sales in Canadian liquor outlets as a predictor of subsequent COVID‐19 infection rates: a time‐series analysis. (12th August 2022) - Stockwell, Tim; Zhao, Jinhui; Alam, Fariha; Churchill, Sam; Shi, Yipu; Naimi, Timothy
Abstract: Aims: Government alcohol sales data were used to examine whether age 15+ per‐capita alcohol consumption (PCAC) (i) changed during COVID‐19 and (ii) predicted COVID‐19 infections 2–5 weeks later. Design: Interrupted time‐series analyses were applied to panels of data before and after COVID‐19 restrictions were introduced in Canada. Setting and participants: The populations, aged 15+, of the provinces of Ontario (ON), British Columbia (BC) and Nova Scotia (NS), Canada. Intervention: Expansion of home delivery options and hours of trading for liquor stores while restrictions on travel, social and economic activities were imposed by governments during COVID‐19 from 17 March 2020 until 29 March 2021. Measurements: Weekly estimates of (i) age 15+ PCAC using sales data supplied by provincial government alcohol distributors for liquor stores, bars and restaurants, (ii) stringency of public health measures assessed by the Public Health Agency of Canada (PHAC) and (iii) new COVID‐19 infections reported by PHAC. Findings: PCAC increased by 7.10% ( P  = 0.013) during the pandemic versus previous years, with increased private liquor store sales partly offset by reduced bar/restaurant sales. Consumption was positively associated with stringency of public health measures. Weekly PCAC was positively associated with new COVID‐19 infections 2 weeks later (+6.34% for a one drink/week increase, P  < 0.001). Lagged associations with COVID‐19 infections 2 or 3 weeks later were observed for PCAC from all sales channels, with larger effect sizes per standard drink/person/week increase for on‐premise outlets (+77.27% week 2, P  = 0.009) than government liquor stores (+6.49%, week 2, P  < 0.001) or private liquor stores (+7.13%, week 4, P  < 0.001). Conclusions: Alcohol consumption increased in three Canadian provinces during COVID‐19 to degrees corresponding to the extent of the strictness of measures imposed to prevent viral spread. Increased consumption of alcohol was associated with increased COVID‐19 infection rates 2 weeks later.